Pendampingan Peningkatan Kualitas Aksi Nyata Pada Plafon Merdeka Mengajar Melalui Pemanfaatan Artificial Intellegence (AI) - Desi Armi Eka Putri; Ikhwan; Merika Setiawati; Miftahul Jannah; Ririn Septya Yunita; Arman Ririnni (LPPM Universitas Ekasakti, 2024)
SMPN 4 Kubung teachers already have good basic competencies but are lacking in maximizing technology with limited training. Apart from that, the school already has classroom facilities equipped with projectors and infocus screens, as well as the availability of other devices such as 15 units of computers, 15 units of chrome books and 82 units of tablets. So with the availability of these facilities their use has not been maximized in the learning process. The process, through the PKM program implemented, namely the use of technology supported by smart boards and AI, will create more interactive digitalization era learning. Method of implementing socialization service, training for 15 teachers, application of AI technology in the learning process at SMPN 4 Kubung, mentoring and evaluation. The implementation of the service program at SMPN 4 Kubung with a focus on improving real action documents showed significant results. The results of accurate data analysis from the implementation of community service at SMPN 4 Kubung show that the application of AI technology significantly improves the quality of real action documents prepared by teachers. By utilizing applications such as ChatGPT, Gemini, Canva, Quizizz, and Wordwall, teachers can produce more structured and informative documents. The community service activity with the title